If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
y/2-((4*y)/5) = 9/10 // - 9/10
y/2-((4*y)/5)-(9/10) = 0
y/2+(-4/5)*y-9/10 = 0
-3/10*y-9/10 = 0 // + 9/10
-3/10*y = 9/10 // : -3/10
y = 9/10/(-3/10)
y = -3
y = -3
| 2b-5/7=b/3 | | 4x-13=x+20 | | 2y=-7x+22 | | n/6=2/9 | | 26=35e+20 | | 22-22=0 | | 26=35e+20(e-1) | | P=2(l+p) | | x=w+y | | 26=35e+20(1-e) | | 10x+27=17x | | 26=e(35+20) | | 2y+x-30=180 | | y/6=3/8 | | ln(x+3)-lnx=5 | | (x^2+3y)*(2x+3y)= | | 6x^2+6x-15=34-29x | | 4y=-5x+20 | | 2x-5x=6x-3x-3x | | -32/21y=-16/63 | | 4y=5x+-20 | | Ln(x+3)-lnc=5 | | 5x(x+60)= | | (5x-3)(3x+7)=0 | | 9.2=-log(x) | | 5x^2+5y^2=16 | | 37+26+3s=21 | | h(4x)=3x^2-2 | | 6-1/-3-(-1) | | 4(4)+1=17 | | .50(18x-10)=3x+x+6-2 | | 5x^2+6x-13=41-31x |